Analyze Factors, Based of Midwife’s Perspective, That Influenced Pre-Natal Visits at Public Health Center - Pereira, Natalia; Carvalho de Araujo, Eugénia; da Costa Monteiro, Ermelinda; Jose Tilman, Etelvina; Dionisio Ximenes, Jose; Oqui, Maximiano (Rifa'Institute, 2024)
Introduction: Pregnancy is a period of growth and development of embryo inside women. Some risk factors of the maternal mortality are related to the lack of women (mothers)’s participation in the consultation of the pre-natal care. Objective: of this thesis was to analyze factors, based of midwife’s perspective, that influenced pre-natal visits at Public Health Center of Comoro, Dili district. Method: used for this study was descriptive study and qualitative approach, and used a questioner for midwives in CHC Comoro. Result and Discussion: Data from Comoro health center; average age of midwives: 37, Majority education: Diploma I, Prenatal consultation importance: very important (100%), Prenatal consultation disclosure importance: very important (70%), Midwives' opinion on the factors of late visits of pregnant women: lack of knowledge of prenatal care (85%), Aspects considered important during the pre-natal consultation visit: tests for Sexually Transmitted Diseases and medical referral if positive (70%), Types of pre-natal consultation disclosures considered adequate: health education measures with the population (90%). Conclusion: My current job requires me to address a range of challenges and enables me to understand the importance of inquiry in the field of maternal health and midwifery and to understand the application of its outcomes that can drive positive change in midwifery care and teaching practice